Case Report: Food Protein-Induced Protein Losing Enteropathy (FPIPLE) in Infancy - Feketea, Gavriela; Popp, Alina; Ionescu, Daniela Marcela; Berghea, Elena Camelia (Frontiers in Nutrition, 2022)
Food-protein induced protein-losing enteropathy (FPIPLE) is a mixed IgE and non-IgE food allergy in infants along with eosinophilic gastrointestinal (GI) diseases (EGID). It is characterized by poor weight gain, edema, due to hypoproteinemia/hypoalbuminemia by enteral loss of proteins, anemia, eosinophilia, raised fecal α1-antitrypsin (α1AT),, and specific-IgE and allergy skin prick test (SPT) positive for offending foods. Here, we describe 4 cases with the same clinical pattern (edema due to hypoproteinemia/hypoalbuminemia from enteral loss of proteins, confirmed by high α1AT in the stools and no other pathological findings explaining the hypoproteinemia including normal kidney and liver function parameters), and propose the term “food-protein induced protein-losing enteropathy” (FPIPLE) to define this clinical entity. We also propose diagnostic criteria and an empirical algorithm of a practical approach to the diagnosis and management for children suspected to have FPIPLE. These infants can be managed successfully with dietary modification. In our 4 cases, initially, an empirical elimination diet was applied, comprising the foods that had benn introduced in the infant's diet during the last month and, an extensively hydrolyzed or elemental formula was given. In a second approach, after evaluation by a pediatric allergist, an allergy test-directed dietary elimination alimentation was implemented, for mother and/or infant. It has yet to be demonstrated whether patients with FPIPLE are a subset of patients with EGID, and whether early intervention modifies the natural course.